Transfer learning based industrial steel plates fault diagnosis using industrial fault signals - Mizan, Mubasshira; Nilo, Laila Sumiya Khan; Tuli, Mosrika Momin (Brac University, 2024)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science, 2021.